Comparative analysis of the organelle genomes of seven Rosa species (Rosaceae): insights into structural variation and phylogenetic position - Zhang, Rongxiang; Liu, Shuwen; Liu, Ying; Wei, Pei; Xiang, Niyan; Zhao, Yuemei; Gao, Xiaoman; Yin, Yebing; Qin, Lijun; Yuan, Tao (Frontiers in Plant Science, 2025)
IntroductionThe genus Rosa belongs to the family Rosaceae within the order Rosales, which is one of the more ancient plant lineages. At present, the complete mitochondrial genome of Rosa spp. is still rarely reported, and studies on the mitochondrial genome of Rosa spp. are limited.MethodsIn this study, the R. laevigata mitochondrial genome was sequenced using both Pacbio Sequel II and DNB-SEQ-T7 platforms. The second- and third-generation data for the other five Rosa species were downloaded from the NCBI database. Genome annotation was performed using Geneious, with structural visualization via CPGview. In-depth analyses were conducted, including assessments of non-synonymous/synonymous mutation ratios (Ka/Ks), codon usage bias, collinearity, and the identification of homologous fragments between chloroplast and mitochondrial genomes. Finally, we employed the maximum likelihood (ML) methods to analyze the phylogenetic relationships among R. laevigata and other Rosa species.ResultsThe chloroplast genome sizes ranged from 156,342 bp (R. laevigata) to 157,214 bp (R. agrestis). The GC content varied from 37.2% to 37.3%, and the number of genes ranged from 129 to 131. The mitochondrial genomes were all circular, with lengths between 271,191 bp and 338,975 bp, containing 52 to 59 genes. Codon usage analysis indicated a preference for A/T-ending codons in both chloroplast and mitochondrial genes. Four highly differentiated regions (rps19, ndhF, ycf1, and psbM-trnD-GUC) in the plastomes of the 7 Rosa species were identified, which can serve as molecular markers for future species identification and studies of genetic diversity. Compared to PCGs of plastome, mitochondrial PCGs displayed a higher non-synonymous to synonymous ratio. We also observed extensive gene transfer between the mitochondria and chloroplasts, particularly with the rrn16 and rpl23 genes, which are commonly found in Rosa species. These gene transfer events likely occurred in the ancestor of Rosa around 4.46 Mya. Estimates of divergence events indicate that rapid differentiation among Rosa species took place around 4.46 Mya, potentially influenced by the uplift of the Qinghai-Tibet Plateau during the Late Miocene.DiscussionThis study enriches the genetic resources of the Rosa genus and lays the groundwork for the development of molecular markers, phylogenetic analyses, and research into the evolution of organelle genomes.